TEKNIK PENERJEMAHAN LISAN DALAM TRADISI BEKAYAT DI LOMBOK - Safoan Abdul Hamid (MABASAN, 2014)
Sasak ethnic group’s community in Lombok, Nusa Tenggara Barat Province, has an oral tradition of reciting hikayat namely bekayat. During the performance, step of the recitation is followed by interpretation from Melayu language to Sasak. As a part of literary work interpreting, the interpreter applies certain method, technique and ideology. This research is aimed at revealing interpreting technique applied in bekayat performance. Sample of this research is taken from Lombok Barat District, out of three other districts in Lombok. Data collection is conducted through recording and an interview technique. The data are transcribed and then analized by an interlinguistic and descriptive method. Result of the analysis shows that the interpreter of bekayat performance applied three techniques, namely paraphrase, contextual conditioning, and compensation.